2020
DOI: 10.1039/d0cy00724b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in multicopper oxidases: a critical review

Abstract: Multicopper oxidases (MCO), such as laccases and bilirubin oxidases, are catalysts of wide interest to a range of biotechnological applications, especially bioremediation and energy transduction. Many of these processes take...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 301 publications
(396 reference statements)
0
30
0
Order By: Relevance
“…Issues in the communication of the enzyme with the electrode, inappropriate redox potential or chloride sensitivity impose to search for more efficient redox enzymes for O2 reduction [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Issues in the communication of the enzyme with the electrode, inappropriate redox potential or chloride sensitivity impose to search for more efficient redox enzymes for O2 reduction [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…BODs are considered to preserve their enzymatic activity in the presence of Cl À [26]. However, it has been indicated that the presence of chloride ions can also alter the oxidative state of BOD, which leads to a decrease in their activity [45,46]. As shown in Figure 5, after addition of CaCl 2 to the electrolyte solution the catalytic current at the biocathode decreased significantly and reached similar current values as those observed for the bioanode.…”
Section: Biofuel Cell Characterizationmentioning
confidence: 69%
“…In the Mr laccase molecule, both T2 and T1/T3α channels were structurally combined in the T2/T3 center, which corresponds to the catalytic reaction mechanism. [43] Comparison of the amino acid composition of the studied Mr laccase and the laccases of a known structure showed the…”
Section: Structure Analysis Of the Laccase Of M Roridum Vkm F-3565mentioning
confidence: 99%